Adverse Effects of Anti‐Covid‐19 Drug Candidates and Alcohol on Cellular Stress Responses of Hepatocytes. Issue 6 (6th January 2022) - Khalatbari, Atousa; Aghazadeh, Zahra; Ji, Cheng
Abstract : During the pandemic, dexamethasone (DEX), remdesivir (RDV), hydroxychloroquine (HCQ), thapsigargin (TG), camostat mesylate (CaM), and pralatrexate were repurposed drugs for coronavirus disease 2019 (COVID‐19). However, the side effects on the liver associated with the anti‐COVID therapies are unknown. Cellular stresses by these drugs at 0‐30 μM were studied using HepG2, Huh7, and/or primary human hepatocytes. DEX or RDV induced endoplasmic reticulum stress with increased X‐box binding protein 1 and autophagic response with increased accumulation of microtubule‐associated protein 1A/1B‐light chain 3 (LC3‐II). DEX and RDV had additive effects on the stress responses in the liver cells, which further increased expression of activating transcription factor 4 and C/EBP homology protein 1 (CHOP), and cell death. Alcohol pretreatment (50 mM) and DEX induced greater cellular stress responses than DEX and RDV. Pralatrexate induced Golgi fragmentation, cell cycle arrest at G0/G1 phase, activations of poly (ADP‐ribose) polymerase‐1 (PARP) and caspases, and cell death. Pralatrexate and alcohol had synergistic effects on the cell death mediators of Bim, caspase3, and PARP. The protease inhibitor CaM and TG induced autophagic response and mitochondrial stress with altered mitochondrial membrane potential, B‐cell lymphoma 2, and cytochrome C. TG and HCQ induced autophagic response markers of Unc‐51 like autophagy activating kinase, LC3‐II, Beclin1, and Atg5, and severe ER stress marker CHOP. Conclusion: These results suggest that the anti‐COVID‐19 drugs, especially with drug–drug or alcohol–drug combinations, cause cellular stress responses and injuries in the liver cells. Abstract : image